SPE Symposium on Improved Oil Recovery 2008
DOI: 10.2118/110134-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Pore Level Study of MIOR Displacement Mechanisms in Glass Micromodels Using Rhodococcus sp. 094

Abstract: Micromodel experiments have been executed in order to have better insight into the displacement mechanisms allowing Rhodococcus sp. 094 to increase oil recovery. Changes caused by the bacteria in the fluid interfaces and pore walls have been recorded and are presented. The previously suspected mechanisms are further confirmed by the results, but a much better insight into the details of how the process occurs has been obtained and a theory for this process is developed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The mass creation leads to blockage of the pores where the oil phase is present. This result is consistent with results reported by Crescente et al (2008) and Kowalewski et al (2005). As observed through Fig.…”
Section: Flow Pattern Changes With Nspb Cellssupporting
confidence: 94%
See 2 more Smart Citations
“…The mass creation leads to blockage of the pores where the oil phase is present. This result is consistent with results reported by Crescente et al (2008) and Kowalewski et al (2005). As observed through Fig.…”
Section: Flow Pattern Changes With Nspb Cellssupporting
confidence: 94%
“…It is observed that the contact angle is lower in the dynamic system compared with the static system. Crescente et al (2008) conduct a number of experiments in Berea sandstone to build the capillary desaturation curve (CDC) using the SPB cells and increasing rates. The CDC curve shows that if the capillary number, a parameter defined as a dimensionless ratio of viscous to capillary forces, is less than 3 × 10 −5 , the residual oil saturation (S or ) is 30 %.…”
Section: Fig 2 Bacteria In Clumps-spb Cells (Left) and Loose Bacterimentioning
confidence: 99%
See 1 more Smart Citation
“…Biosurfactants are able to lower the interfacial tension (IFT) that is responsible for trapping oil in the reservoir. This reduction in IFT will lead to tremendous hydrocarbon mobilization and recovery from porous matrix (Austad and Taugbol, 1995;Green and Wilhite, 1998;Crescente et al, 2008;de Gusmao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%